Kinetics pathway of precipitation in model Co-Al-W superalloy. (15th February 2018) - Azzam, A.; Philippe, T.; Hauet, A.; Danoix, F.; Locq, D.; Caron, P.; Blavette, D.
Abstract: The early stages of precipitation of the γ′ phase in a model Co based superalloy (Co-9.1Al-7W (at.%)) have been investigated at 900 °C using electron microscopy and atom probe tomography. Nucleation, growth and coarsening stages have been studied with a focus on the temporal evolution of the precipitate composition in the light of recent theoretical developments on phase separation in multicomponent alloys. The experimental data have been confronted to the theories of nucleation and coarsening recently developed for such alloys, which are valid for non-ideal and non-dilute systems, and predict the temporal evolution of both the matrix and precipitate compositions. The rate constant for the mean size evolution of the particles, as derived from experiments, has been compared to the one predicted by the mentioned coarsening theory that accounts for a more accurate description of the thermodynamics of the phases, as compared with more classical approaches. From this comparison the γ/γ′ interfacial energy was derived and found equal to ∼48 mJ/m 2 The exponents for the temporal evolution of average particles size, number of particles per unit volume were found identical to those for binary alloys during the coarsening regime, as expected, and the temporal evolutions of compositions in both γ and γ′ phases were found to evolve as predicted by theory. Indeed, the W content in the particles, measured from atom probe tomography (APT) experiments, was found to significantly decrease with time and the observed evolution is remarkably well described by the theory and therefore is shown to originate from the competition between diffusion and capillarity. Graphical abstract: Image 1